Study on Application of Design Criteria on the Openstage of Latest Rooms and Displays in Gianyar, Bali - Krisnha, Ida Bagus Gde Wira; Paturusi, Syamsul Alam; Bharuna, Anak Agung Gde Djaja (Journal of A Sustainable Global South; Vol 2 No 1 (2018): February 2018, 2020)
The purpose of Open Stage Anyar in Gianyar is to provide a facility or facilitate activities associated with Balinese tradi-tional performing arts, modern performing arts and various types of performances related to the elements of preserva-tion, development of interests and talents to Balinese arts. Criteria of design to help determine the final outcome of a desired design to match the function of the building. Some things in the review of the Criteria of design which includes layout and appearance of the building. the spatial arrangement shows the results of macro and micro-based analysis of the site and and the activities in it. In terms of appearance the building gives an impression or atmosphere that re-flects local knowledge of an area and can also make people become interested when looking at the view of the build-ing. Index Terms — open stage, arts, performances.